The Effect of Service Quality on Customer Satisfaction by Moderation of Organizational Culture and Price in View of ISO/IEC 17025:2017 - Nilda Tri Putri; Elita Amrina; Alizar Hasan; iswahyuningsih iswahyuningsih (Jurnal Rekayasa Sistem Industri, 2022)
Quality is an important thing to be discussed anywhere and anytime. Service quality is a determining factor in satisfying customers to achieve economic improvement. Based on previous research, it was found that there is a relationship between organizational culture and customer satisfaction. The quality culture in a laboratory organization reflects the overall organizational culture. This is in line with the ISO/IEC 17025:2017 which requires the application of a quality culture in a calibration laboratory. Price is also an element that needs to be analyzed to achieve customer satisfaction in a calibration laboratory. This study aims to analyze the effect of service quality on customer satisfaction by moderating organizational culture and prices in an ISO/IEC 17025:2017 accredited laboratory in the province of West Sumatra. The data was collected by distributing questionnaires to 93 respondents from government agencies and private companies in West Sumatra. Then, the data was processed using the method of Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this study indicate that service quality, organizational culture, and price have a positive and significant effect on customer satisfaction in a calibration laboratory. Moderation of organizational culture and price have no significant effect on the relationship of service quality to customer satisfaction in a calibration laboratory.